2015
DOI: 10.1017/s0954579414001308
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differential susceptibility in literacy-delayed children: A randomized controlled trial on emergent literacy in kindergarten

Abstract: In this randomized controlled trial, 508 5-year-old kindergarten children participated, of whom 257 were delayed in literacy skills because they belonged to the lowest quartile of a national standard literacy test. We tested the hypothesis that some children are more susceptible to school-entry educational interventions than their peers due to their genetic makeup, and thus whether the dopamine receptor D4 gene moderated intervention effects. Children were randomly assigned to a control condition or one of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…We have therefore begun testing the hypothesis that, for susceptible children (i.e., whose performance depends more strongly on the quality of educational input than for others; Belsky et al, 2007), multimedia books that provide intensive, closely monitored, and individualized scaffolding may be especially effective in turning a putative "risk" group into a successful group. The experiment (Plak, Kegel, & Bus, 2014) was carried out at 82 Dutch schools. All 5-year-olds who belonged to the lowest quartile of a national standard literacy test were eligible to participate in this experiment.…”
Section: Questions and Comments Modeled On Co-reading With Adults Canmentioning
confidence: 99%
“…We have therefore begun testing the hypothesis that, for susceptible children (i.e., whose performance depends more strongly on the quality of educational input than for others; Belsky et al, 2007), multimedia books that provide intensive, closely monitored, and individualized scaffolding may be especially effective in turning a putative "risk" group into a successful group. The experiment (Plak, Kegel, & Bus, 2014) was carried out at 82 Dutch schools. All 5-year-olds who belonged to the lowest quartile of a national standard literacy test were eligible to participate in this experiment.…”
Section: Questions and Comments Modeled On Co-reading With Adults Canmentioning
confidence: 99%
“…Research on genetic moderation of intervention efficacy is growing following a pioneering study showing that video-feedback intervention designed to reduce externalizing behavior by promoting sensitive parenting and positive discipline proved effective only for children carrying 7-repeat alleles of the DRD4 gene (Bakermans-Kranenburg et al, 2008). More recent research further revealed that children carrying the 7-repeat allele disproportionately benefited from computerized training designed to enhance phonemic awareness (Kegel, Bus, & van IJzendoorn, 2011) and, separately, text comprehension (Plak, Kegel, & Bus, 2015). Working with older children-African American adolescents growing up in rural Georgia- Brody, Yu, and Beach (2015) observed that a family-based intervention designed to prevent, among other things, substance use proved effective principally for teenagers carrying this same putative plasticity allele.…”
Section: Gene 9 Intervention Interactionmentioning
confidence: 99%
“…The reading motivation of the fifth graders in this study did not change due to reading in digital format, nor did they learn more new vocabulary than their peers reading hardcopy print books. However, we did find support for the notion that susceptible students benefit from the presence of a pedagogical agent (e.g., Kegel et al, 2011;Plak et al, 2015). Susceptible students who read digital books with guidance from a PA Figure 3.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, accumulating evidence (Kegel et al, 2011;Plak et al, 2015) including the results presented in this article suggest that for a minority of children (carriers of the DRD4 seven-repeat allele) learning outcomes are strongly dependent on the presence or absence of guidance. In the present study, it was shown that guidance provided by a PA helps susceptible students to learn more from reading.…”
Section: Discussionmentioning
confidence: 81%